Analysis of the Strategy for the Implementation of Klik Indomaret E-Commerce Application in Improving the Quality of Consumer Service - Asrawan Asrawan; Cholifatul Sholikah (International Journal of Management Science and Information Technology, 2026)
The development of digital technology has driven significant changes in the modern trading system, including in the retail sector. Klik Indomaret, which is one of the e-commerce platforms owned by PT Indomarco Prismatama, is trying hard to maximize its digital services. The goal is because they can meet the demand of fast-paced consumers in today's era. This research was conducted to see the extent to which the strategy of using the Klik Indomaret application is successful in improving the quality of service to customers. The method used in the study is a qualitative descriptive approach by conducting in-depth interviews directly who are considered to have knowledge and experience in the implementation of the Klik Indomaret E-commerce application which is relevant to the quality of service. The results of this study show that the quality of electronic services (e-service quality) is considered quite good, especially for ease of application, but there are still obstacles faced by customers regarding customer service responses which are sometimes not fast. To overcome this problem, Klik Indomaret innovates by providing a real-time order tracking feature.